Financial inclusion and the growth of small medium enterprises in Uganda: empirical evidence from selected districts in Lango sub-region - Eton, Marus; Fabian, Mwosi; Constant, Okello Obura; Abanis, Turyahebwa; Gilbert, Uwonda (Journal of Innovation and Entrepreneurship, 2021)
The growth and failure of small and medium enterprises has been a topic of discussions world over among policymakers and researchers. This study was guided by the following objectives: to examine the contributions of small medium enterprises (SMEs), to determine the challenges affecting small medium enterprises, to examine how financial inclusiveness supports the growth of small medium enterprises, and to establish the relationship between financial inclusion and growth of small medium enterprises. The study used a cross-sectional research design. Descriptive design was used and supplemented by inferential statistics. Correlation and regression analysis were adopted. The study revealed that financial inclusion is significant in supporting SME growth. The study further also revealed that the cost of acquiring and servicing financial services is high; there is also difficulty in using some of the financial services, and the way financial providers treat financial users, some lacked some degree of respect and dignity. The study recommends that financial providers should continue sensitizing the public on the available financial services beyond credit services, which are common and known. Digital financial service providers should encourage their clientele to use digitalized financial services which are cheap, secure, and risk averse. The cost of capital should also be reduced to encourage borrowing while SMEs should innovatively produce goods that can be competitive at both domestic and international markets.